2009
DOI: 10.1123/jpah.6.5.625
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Leisure, Transportation, Occupational, and Household Physical Activity: Prevalence and Associated Factors

Abstract: Background:To estimate the prevalence of and identify factors associated with physical activity in leisure, transportation, occupational, and household settings.Methods:This was a cross-sectional study aimed at investigating living and health conditions among the population of São Paulo, Brazil. Data on 1318 adults aged 18 to 65 years were used. To assess physical activity, the long version of the International Physical Activity Questionnaire was applied. Multivariate analysis was conducted using a hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
100
5
90

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(218 citation statements)
references
References 31 publications
23
100
5
90
Order By: Relevance
“…This instrument was used in epidemiological study with adult representative sample of São Paulo municipality. 3 To evaluate the environment we used an adapted version of the Neighborhood Environment Walkability Scale (NEWS --Brazilian version), validated by Malavasi et al 14 The scale was modifi ed to improve understanding by adult residents of Ermelino Matarazzo. The fi nal adapted version, consisting of 38 questions, was discussed with experts of the environment and physical activity in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…This instrument was used in epidemiological study with adult representative sample of São Paulo municipality. 3 To evaluate the environment we used an adapted version of the Neighborhood Environment Walkability Scale (NEWS --Brazilian version), validated by Malavasi et al 14 The scale was modifi ed to improve understanding by adult residents of Ermelino Matarazzo. The fi nal adapted version, consisting of 38 questions, was discussed with experts of the environment and physical activity in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the proportion of individuals who meet the recommendations for walking and MVPA during leisure time was small (18%) and similar to the results shown by the Vigitel study for the population of the city of Curitiba (16.1%). b A total of two studies were conducted in Brazil, aiming to observe the practice of physical activities during leisure time and using the same instrument of the present study, one with 1,318 adults of the city of São Paulo, SP, 9 and another with 972 adults of the city of Pelotas, RS. 2 In these studies, higher proportions of individuals meeting the current recommendations were found: 22.5% and 30.2%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Buscando reverter o quadro da baixa prevalência da prática de atividade física (AF) em adultos brasileiros tanto no tempo de lazer, como na forma de deslocamento 1 , o Sistema Único de Saúde (SUS) intensificou o desenvolvimento e a disseminação de ações, programas e políticas para promover a AF no nível populacional. Considerando que, aproximadamente 80% da população brasileira depende exclusivamente do atendimento oferecido pelo SUS e a inserção da prática de AF enquanto um dos fatores determinantes da saúde no trabalho de promoção da saúde e prevenção de doenças 2,3 , este cenário amplia a perspectiva de um impacto benéfico gradual nos próximos anos para a saúde pública.…”
Section: Introductionunclassified